Assimilable organic carbon removal strategy for aquifer storage and recovery applications - Hien Thi Nguyen; Kim, Youngjae; Choi, Jae-Woo; Cho, Kyungjin; Jeong, Seongpil (Academic Press, 2020)
Aquifer storage and recovery (ASR) technology has been adopted as a strategic water management tool. However, during the injection of oxic and organic carbon-containing water to the underground aquifers, severe phenomena such as clogging and groundwater deterioration have been reported. To prevent these severe phenomena, assimilable organic carbon (AOC) concentration has been controlled in the ASR applications by supporting bacteria growth potential. In this study, the AOC removal strategy was investigated in a simulated ASR system using an indigenous bacterium, Pseudomonas jinjuensis. AOC removal was evaluated under three different experimental conditions: (i) 30 degrees C and aerobic, (ii) 15 degrees C and aerobic, and (iii) 15 degrees C and anoxic. The effects of contact media such as sand and granular activated carbon on AOC removal efficiency were also investigated. Results show that under the 30 degrees C aerobic condition, P. jinjuensis could remove 99.8% (13 mu g L-1) of AOC with soil. The variations in the organic fractions determined by liquid chromatography with organic carbon detector analysis were observed and showed trends similar to those of AOC determined by the flow cytometry method. The indirect injection method in ASR application was recommended due to the AOC removal benefit by soil indigenous bacterium.